Unsteady Boundary Layer Stagnation Point Flow and Heat Transfer over a Stretching Sheet in a Porous Medium with Slip Effects - Rosali, Haliza; Badlilshah, Mohd Noor; Mohamat Johari, Mohamat Aidil; Bachok, Norfifah (CFD Letters, 2020)
Boundary layer flow and heat transfer over a stretching sheet in a porous medium has many applications in industrial processes. The effect of porosity plays a significant role in determining the behaviour of the fluid flow. Based on that, we analyzed the unsteady boundary layer stagnation point flow and heat transfer towards a stretching sheet by considering the porosity. The velocity and thermal slip effects are taken into consideration in the present analysis. The governing non-linear partial differential equations were transformed into a system of nonlinear ordinary differential equations using similarity transformation. The resulting ordinary differential equations were solved numerically using the shooting method in Maple software. Numerical results for the dimensionless velocity profile, temperature profile, skin friction coefficients and the local Nusselt number are presented for various parameters. The effect of dimensionless material parameter, thermal slip effect and velocity slip effect on the flow field is also discussed. It is found that the skin friction coefficients decrease whereas the local Nusselt number increases with the increase in permeability parameter.